Dynamics of Vaginal Microbiota during Estrous Cycle and its Association with Reproductive Hormones in Bubalus bubalis - P, Mahesh; Suthar, Vishal S.; Patil, Deepak B.; Bagatharia, Snehal B.; Joshi, Madhavi (Indian Journal of Veterinary Sciences and Biotechnology, 2021)
This experiment aimed to evaluate the dynamics of vaginal microbiota during different estrous cycle stages in cyclic buffalo heifers using metagenomic analysis and its association with estradiol (E2) and progesterone (P4) hormones. Out of nine buffalo heifers, eight responded to ovsynch protocol were included in the trial. Vaginal flushing was carried out using the assembly of sterile normal saline with a syringe and AI sheath on day 0 (estrus), day 4 (metestrus), day 9 (diestrus), and day 18 (proestrus) of the estrous cycle followed by blood sample collection. The vaginal flushing was lyophilized, DNA were isolated and amplified with Phusion primer for bacteria (16S rRNA), fungus (ITS 6-8), and archaea (16S rRNA). The amplicon library was constructed, sequenced, and annotated through MG-RAST server with RNA database SILVA ssu with 98% identity. The results of the study revealed four major domain- bacteria (93.8%), eukaryota (5.7%), archaea 0.006% and unclassified sequences (0.41%). A total of 2196 bacterial species, 17 fungal and two archaeal species, were detected, confirming the rich diversity of vaginal microflora in buffalo heifers. The highly abundant domain of bacteria contained 18 bacterial phyla, which were grouped into four high (>5%), six moderate (0.1-5%) and eight less abundant groups (0-0.1%); and it contained 589 genera of which Amycolatopsis, Cardiobacterium, Cellulomonas, Pimelobacter, Rickettsia, Promicro-monospora, Xanthobacter, Anerotruncus, Desulfonispira, Leptospira and Massilia were significant. The two fungal phyla detected were Ascomycota and unclassified fungi. Out of 589 bacterial genera, 48 genera showed positive correlation and four genera showed negative correlation with plasma P4. The results of fold change in Log2 values and association of E2 and P4 hormones with high and less abundant phyla and genera of bacteria during four phases suggest dynamics of vaginal microbiota during the estrous cycle. Though the present study demonstrated novel findings and is the first of its kind in buffalo heifers, it warrants further research.